The Potential Roles of Pharmacists in the Clinical Implementation of Pharmacogenomics - Abdullah Al Maruf; Md. Abdul Aziz (MDPI AG, 2023)
The field of pharmacogenomics is at the forefront of a healthcare revolution, promising to usher in a new era of precision medicine [...]